2019
DOI: 10.1007/s00414-019-02011-6
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem proteomics to discover biomarkers for forensic PMI estimation

Abstract: The assessment of postmortem degradation of skeletal muscle proteins has emerged as a novel approach to estimate the time since death in the early to mid-postmortem phase (approximately 24 h postmortem (hpm) to 120 hpm). Current protein-based methods are limited to a small number of skeletal muscle proteins, shown to undergo proteolysis after death. In this study, we investigated the usability of a target-based and unbiased system-wide protein analysis to gain further insights into systemic postmortem protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 35 publications
(40 reference statements)
7
43
0
Order By: Relevance
“…Especially, the loss of the metavinculin band, occurring at day 3 in all animals, confirms the results of previous pilot experiments on pigs and humans [53] and quantitative experiments on rats [54]. Also, the loss of native vinculin and the appearance of degradation products have been reported [53,54]. However, in this particular study, these changes occurred in the later stages of the experimental series in which only a small sample size was available, thus producing large confidence intervals.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Especially, the loss of the metavinculin band, occurring at day 3 in all animals, confirms the results of previous pilot experiments on pigs and humans [53] and quantitative experiments on rats [54]. Also, the loss of native vinculin and the appearance of degradation products have been reported [53,54]. However, in this particular study, these changes occurred in the later stages of the experimental series in which only a small sample size was available, thus producing large confidence intervals.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, the present results show the potential of this protein for future application in PMI estimations. Especially, the loss of the metavinculin band, occurring at day 3 in all animals, confirms the results of previous pilot experiments on pigs and humans [53] and quantitative experiments on rats [54]. Also, the loss of native vinculin and the appearance of degradation products have been reported [53,54].…”
Section: Discussionsupporting
confidence: 87%
“…In a following study, in 2016, Pittner et al [45] analyzed human postmortem skeletal muscle samples, which revealed similar results to previously conducted porcine study, and showed a predictable protein degradation processes in human muscle. Recently a study by Choi et al [46] investigated the ability of usage unbiased protein analysis to find out the postmortem protein changes and detect new possible markers for PMI estimation. They used proteomic profiling of rat and mouse skeletal muscle samples using MS-based proteomic method.…”
Section: Postmortem Intervalmentioning
confidence: 99%
“…Pittner at al. [44] Pittner et al [45] MS-based proteomics Choi et al [46] Handke et al [47] Procopio et al [49] Prieto-Bonete et al [50] Intoxication and abuse of drugs MS-based proteomics Bittencourt et al [51] Diagnosis of disease and cause of death MS-based proteomics Broadbelt at al. [53] Palmiere et al [54] Immunohistochemistry Unkrig et al [55] Mustafa et al [56] Fineschi et al [57] Edston and van Hage-Hamsten [58] Genomics Detection of the biological specimens PCR Nakanishi et al [12] Postmortem interval PCR Pechal et al [19] Intoxication and abuse of drugs PCR Sallaee et al [62] Ikematsu et al…”
Section: Sds-page Western Blotmentioning
confidence: 99%
“…For instance, useful methods for differential diagnosis between freshwater and saltwater drowning have been reported [ 10 , 11 , 12 , 13 , 14 ]. Novel technologies such as proteomics are still in the stage of exploration in forensic pathology [ 15 ], and mainly focused to determine PMI [ 16 , 17 , 18 ]. We proposed to investigate the usefulness of MS-based spectrometry to identify biomarkers that add relevant information in the postmortem diagnosis of drowning and the circumstances of the death.…”
Section: Introductionmentioning
confidence: 99%